Beam-reconfigurable of a planar parasitic pixel antenna for X-band radar application - Subramaniam, Devakumaran (School of Computer and Communication Engineering, 2018)
Literature review about reconfigurable antenna had been done in order to understanding the design concept and for the parasitic pixel antenna. Besides that, the combination of driven parasitic and pixel had been studies before proceed with the design. In this research, three type of antenna had been proposed, consist of driven pixel antenna, driven parasitic antenna and combination of driven parasitic pixel antenna. All this antenna will be applied by the Yagi-Uda technique that already being proved for the parasitic and pixel antenna. All the design had been simulated by using CST Microwave Studio software. Once achieve the optimal result from the simulation then all the antennas are fabricated using Taconic substrate with dielectric constant of 2.2. All the prototypes is tested and measured using KEYSIGHT EN5234 PNA-L Network Analyzer and Atenlab (OTA-500) Chamber, for measuring the return loss and beam steering pattern. Then, the results were analyzed based on simulation and measurement of the antenna on the return loss, gain, beam steering pattern and etc.